TOWARDS THE REALISATION OF JUSTICE IN THE NIGER DELTA: A SOCIO-LEGAL PERSPECTIVE (The Pretoria Student Law Review, 2021)
Apart from the brutal Nigerian civil war (1967 - 1970), nothing else has captured the conscience of the people of the world, vis-à-vis the Nigerian Federation, more than the plight of the people of Niger Delta. It remains the open sore (to borrow Wole Soyinka’s phrase) of the Nigerian Federation. The devastating impact of oil exploration in the area has wreaked havoc of immeasurable proportions on the health, socio-economic and environmental conditions of the people. From the short-lived armed struggle of the late Isaac Adaka Boro in the 1960’s, to the civil resistance method of the late Kenule Saro Wiwa in the early 1990’s, and the present guerrilla tactics of the Movement for the Emancipation of the Niger Delta (MEND), the issue of the Niger Delta continues to beg for more constructive attention. This paper aims to ascertain the (in)justice in the Niger Delta through an examination of the concept of justice, and subsequently to recommend strategies for redressing the inherent anomalies.
Keywords: Niger Delta; oil exploration; health; socio-economic; environmental conditions; (in)justice